Perceived challenges in open and distance learning among nursing students of Open University Malaysia: A descriptive analysis - Saedah Muda; Yee Bit-Lian (2019)
Open and distance learning (ODL), a structured learning whereby the students and instructors are separated by time and place, is currently the popular trend among working adults across the nation. From higher nursing education perspective, it must be made accessible, affordable and flexible to allow the nurses to cope with the demands and pressure of busy work and family commitments that give rise to several challenges. Hence, the main objective of this study is to examine perceived challenges in ODL among undergraduate nursing students of Open University Malaysia (OUM). The study employed quantitative approach by using close-ended questionnaires. A convenience samples of registered nurses (RNs) undertaking Bachelor of Nursing Sciences (BNS) programme (n = 81) completed the face-to-face questionnaires. Data analysis using descriptive statistics collected from 81 respondents from five OUM learning centres. The perceived areas of challenges were grouped into: perceptions of ODL for continuing education; perceived challenges facing ODL students; instructional related challenges; and institutional related challenges. Surprisingly, the findings indicate that BNS students are facing only some extent of challenges in their learning particularly within their own circles with perceived challenge highest on financial constraints (54.3%). However, they demonstrate positive perception of ODL for continuing education with the majority (70.4%) agreeing that it is relevant with current teaching-learning strategy. There is no obvious indication of perceived challenges instigates from instructional and institutional factors as the majority disagree (51.9%) that they are facing unhelpful course information and lack of direction; and (46.9%) disagree lack / delayed of important information, respectively. Above all, the findings address students’ concerns in improving student experiences, and enhanced instructional and institutional contributions that marked the achievement of ODL outcomes. In essence, this study has shed some light into challenges faced by ODL nursing students and the strategies to further ameliorate the implementation of ODL. (Abstract by authors)